ACUTE CENTRAL TYPE FACIAL PARALYSIS AS A RARE MANIFESTATION OF CEREBRAL ARTERY STROKE MEDIA - Kandisa, Dayinta Drasti (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Acute central type facial paralysis is a rare manifestation of cerebral artery media stroke (MCA) that is often misdiagnosed as Bell's palsy. This article discusses the case of a 40-year-old woman with a swollen face to the right and a deviation of the tongue to the left without weakness of the extremities, as well as hypertension at onset. The diagnosis of Bell's palsy is questionable due to the involvement of nerve XII and vascular risk factors. Lesions in the primary motor cortex or corticobulbar tract, supplied by a specific branch of MCA, are the main cause of this condition. About 3-7% of acute MCA strokes show central-type facial paralysis as the main symptom. Management includes the administration of antiplatelets, while corticosteroids are not recommended in ischemic stroke. The prognosis of this case tends to be good compared to MCA stroke with extensive neurological deficits, but the risk of recurrence is high if vascular risk factors are not controlled. This study confirms the importance of vigilance against atypical manifestations of stroke, especially in patients with hypertension or other vascular risk factors. Proper diagnosis, appropriate management, early rehabilitation, and secondary prevention play a major role in improving clinical outcomes and preventing stroke recurrence.